EFFECTIVENESS OF APPROACH TO LEARNING DISCOVERY MODEL TOWARD MATHEMATICAL DISPOSITION - Elisa Firdaus; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2019)
The low mathematical disposition of students became a problem in this study. The use of guided discovery models in mathematics learning is expected to be effective in increasing mathematical dispositions. This study aims to determine the effectiveness of guided discovery learning models on grade VII students' mathematical disposition in State Junior High School (SMPN) 1 Pajangan even semester 2017/2018 school year. This study's population was students of class VII of SMPN 1 Pajangan of 2017/2018 school year consisting of 5 classes. The sampling technique uses random cluster sampling, which is sampling by random class through a lottery. Students of class VII D obtained the lottery results as the experimental group and students of class VII A as the control group. Data collection techniques in the form of tests and questionnaires. Data collection instruments in the form of test questions and form questionnaires with Likert scale. Data analysis techniques using t-test. Hypothesis testing uses a two-party t-test and a one-party t-test. The results showed: 1) Test the first hypothesis through the test obtained , and through the questionnaire obtained Â then H0 has rejected means that there are differences in students' mathematical disposition abilities in classes that use guided discovery learning models with students in classes that use expository learning models. 2) Test the second hypothesis through tests obtained Â and through questionnaires obtained Â H0 has rejected guided discovery learning models that are more effective than expository learning models on students' mathematical dispositions.